Exosomes with membrane‐associated TGF‐β1 from gene‐modified dendritic cells inhibit murine EAE independently of MHC restriction. Issue 9 (21st June 2013) - Yu, Lei; Yang, Fei; Jiang, Lingling; Chen, Yinghu; Wang, Keyi; Xu, Feng; Wei, Yinxiang; Cao, Xuetao; Wang, Jianli; Cai, Zhijian
<x xml:space="preserve">Abstract</x> We have previously demonstrated that exosomes from dendritic cells (DCs) secreting TGF‐β1 (sTGF‐β1‐EXOs) delay the development of murine inflammatory bowel disease (IBD). In this study, we isolated exosomes from DCs expressing membrane‐associated TGF‐β1 (mTGF‐β1‐EXOs) and found mTGF‐β1‐EXOs had more potent immunosuppressive activity than sTGF‐β1‐EXOs in vitro. Treatment of mice with mTGF‐β1‐EXOs inhibited the development and progression of myelin oligodendrocyte glycoprotein (MOG) peptide‐induced EAE even after disease onset. Treatment of mice with mTGF‐β1‐EXOs also impaired Ag‐specific Th1 and IL‐17 responses, but promoted IL‐10 responses ex vivo. Treatment with mTGF‐β1‐EXOs decreased the frequency of Th17 cells in EAE mice, which might be associated with the down‐regulation of the p38, ERK, Stat3, and NF‐κB activation and IL‐6 expression in DCs. Treatment with mTGF‐β1‐EXOs maintained the regulatory capacity of Treg cells, and adoptive transfer of CD4+Foxp3+ Treg cells from mTGF‐β1‐EXO‐treated EAE mice dramatically prevented the development of EAE in the recipients. Moreover, treatment with mTGF‐β1‐EXOs from C57BL/6 mice effectively prevented and inhibited proteolipid protein (PLP) peptide‐induced EAE in BALB/c mice. These results indicate that mTGF‐β1‐EXOs possess powerful immunosuppressive ability and can effectively inhibit the development and progression of EAE in different strains of mice.